Benefit Incidence of Public Spending on Education in the Philippines - Rosario G. Manasan; Janet S. Cuenca; Eden C. Villanueva-Ruiz (Philippine Institute for Development Studies (PIDS), 2008)
Government education spending is expected to improve the well-being of beneficiaries and enhance their capability to earn income in the future. In this sense, directing education expenditures to the poor holds a promise for breaking the intergenerational transmission of poverty. Given this perspective, the paper addresses the question: to what extent has the poor benefited from government spending on education? In particular, it uses benefit incidence analysis to evaluate whether expenditures on education had redistributive impact.
Keywords: 330; targeting; education; poverty reduction; benefit incidence analysis; Gini coefficient; concentration coefficient; concentration curve; Bildungsfinanzierung; Bildungsniveau; Armut; Philippinen